Optimized design of complex field network coding scheme in non-orthogonal multiple access relay system - Xi CAI; Ping-zhi FAN; Qing-chun CHEN (Tongxin xuebao)
Wireless relay and network coding are two fundamental techniques to enhance the throughput of wireless communication system.The optimized design of complex field network coding scheme in non-orthogonal multiple access single relay system was addressed.Firstly,given the total transmitting power at all source nodes (equal transmitting power at every source node was assumed) and the relay node,the system might achieve the minimal symbol error probability (SEP) when the total transmitting power were equally allocated to all source nodes and relay node.Secondly,the choice of the complex field network coding coefficients plays an important role in the achieved SEP for the non-orthogonal multiple access single relay system was disclosed,and the optimized coding coefficient design in terms of the maximal coding gain were presented for arbitrary number of source nodes.It was shown that,the similarity of network coded signal of multiple source signals could be effectively avoided by using the optimized coding coefficient,which accounted for the realized performance improvement in the non-orthogonal multiple access single relay system.